A method for screening copper-tolerant rice (Oryza sativa L.) cultivars based on hydroponic experiments and cluster analysis. Issue 12 (2nd December 2017) - Lin, Sen; Yang, Tingting; Zhu, Shaowei; Wang, Jifeng; Ni, Wuzhong
ABSTRACT: A method for screening copper (Cu)-tolerant rice cultivars was studied by combining hydroponic experiments and cluster analysis, and the classification of cultivars in Cu stress tolerance was done. In the first hydroponic experiment, seedlings of Jiahe991 and Xiushui114 were planted in nutrient solution with different Cu 2+ concentrations from 10 to 1800 μg/L. Results indicated that the toxic threshold of Cu concentration in solution ranged from 900 to 1200 μg/L, since SPAD (Soil and Plant Analyzer Development, SPAD-502, a portable chlorophyll meter, Minolta Camera Co. Ltd., Japan) values of leaves and seedlings biomass of the treatments with ≥900 and/or 1200 µg/L were significantly lower than the control. The second experiment was conducted with 16 local rice cultivars under three Cu treatments (10, 1000, and 1500 μg/L). The 16 cultivars were well classified into tolerant, normal, and sensitive groups as a result of cluster analysis based on the relative SPAD (Soil and Plant Analyzer Development, SPAD-502, a portable chlorophyll meter, Minolta Camera Co. Ltd., Japan) value, shoot and root dry weights, root length and root dehydrogenase activity, and oxidizing capacity and shoot Cu concentration. Xiushui123, Xiushui134, Jiahe991, and Xianghu301 belonged to the tolerant group; Xiushui137 belonged to the sensitive group. The cluster analysis based on hydroponic experiments is an effective method for identifying rice cultivars that are tolerant to Cu stress. In addition, four cultivars ( Xiushui123, Xiushui134, Jiahe991, and Xianghu301 ) are recommended in local practice.